Identification of a New Compound as Î±-Glucosidase Inhibitor from Aspergillus aculeatus - Dewi, Rizna Triana; Suparman, Asep; Mulyani, Hanny; Darmawan, Akhmad; Lotulung, Puspa Dewi Narrij (ANNALES BOGORIENSES, 2016)
Terestrial fungi are of great importance as potential sources of pharmaceutical agent. Aspergillus aculeatus, a fungus isolated from soil sample collected in Indonesia, was cultured in liquid media to investigate a novel compound as inhibitor Î±-glucosidase. The mycelium extract of A. aculeatus shows potential activity against Saccharomyces cereviseae Î±-glucosidase and mild activity against mammalian Î±-glucosidase with IC50 values of 9.57 Âµg/mL and 470.76 mg/mL, respectively. Enzyme assay-guided fractionation of this extract afforded rubrofusarin (1). Rubrofusarin, a linear naphtho-Î³-pyrone, is a natural pigment from Aspergillus sp. Interestingly, compound 1 shows potential inhibitory activity against mammalian Î±-glucosidase (IC50 of 92.7 Âµg/mL), but no to S. cereviseae Î±-glucosidase. The results suggest that A. aculeatus is a promising natural source as a lead compound in the discovery of antidiabetic drug.